2016
DOI: 10.17586/2220-8054-2016-7-1-153-157
|View full text |Cite
|
Sign up to set email alerts
|

Study of antioxidant activity of fullerenols by inhibition of adrenaline autoxidation

Abstract: In this paper, we describe application of the adrenaline autoxidation reaction to determine the antioxidant activity of fullerenols C 60 , C 70 their mixture with higher fullerenol and endohedral fullerenol Y@C 82 . It was shown that the adrenaline autoxidation reaction can be applied to determine the antioxidant activity of fullerenols. The antioxidant activity of C 70 fullerenol was higher than that of C 60 fullerenol Additionally, the antioxidant activity of Y@C 82 fullerenol was higher than that of C 70 fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Some fullerene derivatives, which mainly include tris-malonyl C 60 (C 3 ) and polyhydroxy fullerene (fullerenols), have excellent antioxidative activity via scavenging free radicals. Fullerenols, which have attached hydroxyl groups (−OH) on fullerene cages, have moderate water solubility and biocompatibility. Chiang et al first found that fullerenols have potential antioxidative properties by which they can scavenge superoxide radical anions (O 2 •– ) generated by xanthine and the xanthine oxidase system . This is especially true for C 60 (OH) 22 , which can scavenge 1 O 2 , O 2 •– , and • OH .…”
Section: Introductionmentioning
confidence: 99%
“…Some fullerene derivatives, which mainly include tris-malonyl C 60 (C 3 ) and polyhydroxy fullerene (fullerenols), have excellent antioxidative activity via scavenging free radicals. Fullerenols, which have attached hydroxyl groups (−OH) on fullerene cages, have moderate water solubility and biocompatibility. Chiang et al first found that fullerenols have potential antioxidative properties by which they can scavenge superoxide radical anions (O 2 •– ) generated by xanthine and the xanthine oxidase system . This is especially true for C 60 (OH) 22 , which can scavenge 1 O 2 , O 2 •– , and • OH .…”
Section: Introductionmentioning
confidence: 99%
“…However, fullerenes are hydrophobic, which limits the possibilities of their direct use in biomedicine [193] It is possible to obtain their aqueous dispersions [194][195][196][197][198][199][200] and associates with organic compounds [200][201][202][203][204][205]. One of the ways of modifying the surface of fullerenes provides hydroxylated derivatives such as fullerenols [195,200,205,206,208]. The specific functionalization of their surface is achieved through the use of amphiphilic polymers, amino acids, carboxylic acids, and biologically active preparations that identify molecules [206,207].…”
Section: Carbon-based Nanostructured Systemsmentioning
confidence: 99%
“…The absorption of such systems by cells can be realized through specific endocytosis. Another possible trend in the use of fullerenes is the creation of bioactive [203,204,206,208] or contrast materials for nuclear magnetic resonance imaging (MRI) through internal functionalization by contrast agents, including Gd 3+ , Sc 3+ , Ho 3+ , Tm 2+ , Ga 3+ and Tc 2+ ions, with isolation of unstable and potentially toxic contrast materials from the internal medium of the body [209][210][211][212]. A similar solution for creating contrast materials is proposed in [213] for Keplerates, the non-carbon analogs of fullerenes which form ionic associates with cations of the above-mentioned metals.…”
Section: Carbon-based Nanostructured Systemsmentioning
confidence: 99%